MOTILITAS DAN ABNORMALITAS SPERMATOZOA DOMBA YANG DIENCERKAN DENGAN LESITIN KACANG KEDELAI (Soybean lecithin) SELAMA PENYIMPANAN PADA SUHU 5°C - Salmin, Salmin (Jurusan Peternakan Fakultas Pertanian Universitas Tadulako, 2012)
The study was conducted to determine the quality of ram spermatozoa diluted with soybean lecithin during storage at 5oC. Semen was collected from three adult rams by artificial vagina then evaluated macroscopically and microscopically. Semen was diluted with soybean lecithin extender 0% (L0), 1% (L1), 2% (L2), 3% (L3) and 4% (L4). Diluted semen samples were stored at 5oC annealing temperature. Motility and sperm abnormalities were then evaluated every day. Treatment of soybean lecithin levels was highly significant (P<0.01) on progressive motility and abnormalities of ram spermatozoa. The highest percentage of progressive motility and the lowest abnormality of ram spermatozoa were respectively 64.48% and 11.27% when level of soybean lecithin used is 3%.